2022
DOI: 10.2196/29227
|View full text |Cite
|
Sign up to set email alerts
|

Our Whole Lives for Hypertension and Cardiac Risk Factors—Combining a Teaching Kitchen Group Visit With a Web-Based Platform: Feasibility Trial

Abstract: Background Hypertension (HTN) affects millions of Americans. Our Whole Lives: an eHealth toolkit for Hypertension and Cardiac Risk Factors (OWL-H) is an eHealth platform that teaches evidence-based lifestyle strategies, such mindfulness and cooking skills, to improve self-management of HTN. Objective The primary goal of this pilot study was to evaluate the feasibility of OWL-H combined with teaching kitchen medical group visits (TKMGVs) in a low-income … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“… 21 Participant characteristics were comparable to the present study, in which most participants had tertiary education. 21 One possible explanation for the higher rate could be that the program combined web-based learning with a face-to-face cooking class every fortnight. Another feasibility study of online education also found a completion rate of 88% after 12 weeks of intervention among 26 participants.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“… 21 Participant characteristics were comparable to the present study, in which most participants had tertiary education. 21 One possible explanation for the higher rate could be that the program combined web-based learning with a face-to-face cooking class every fortnight. Another feasibility study of online education also found a completion rate of 88% after 12 weeks of intervention among 26 participants.…”
Section: Discussionsupporting
confidence: 71%
“…The results of the present study contradicted the findings of another study. 21 Gardiner and colleagues conducted an 8-week pilot study to assess the feasibility of web-based nutrition education for low-income populations with hypertension and reported a high completion rate of 88%. 21 Participant characteristics were comparable to the present study, in which most participants had tertiary education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although more research is needed, emerging evidence suggests produce prescription programs can increase fruit and vegetable consumption and reduce household food insecurity; however, the mixed evidence for effects on diet-related health outcomes (i.e., weight, blood pressure, HbA1c) is in part due to suboptimal redemption rates, short intervention durations, and barriers such as limited employee training at voucher-redemption locations [ 101 •, 102 ]. Similarly, while teaching kitchens are seemingly feasible, participation rates can be low [ 103 ], and few studies have actually assessed hospital-based food pantries [ 101 •]. More evaluations are needed to understand the acceptability, uptake, and potential impact of these interventions among nutrition insecure groups specifically.…”
Section: Healthcare Interventionsmentioning
confidence: 99%